Transformasi PT Bank Syariah Indonesia Tbk Menjadi BUMN: Analisis Komprehensif Perspektif Yuridis, Dampak Ekonomi, dan Syariah - Rachmad Risqy Kurniawan (Journal of Economic and Business Advancement, 2026)
This article examines the institutional transformation of PT Bank Syariah Indonesia Tbk into a state-owned enterprise (BUMN) through a comprehensive conceptual framework integrating legal restructuring, economic governance, and Shariah legitimacy. Employing a non-empirical and interpretative-critical approach, the study synthesizes international literature on corporate governance, economic analysis of law, and Islamic finance, alongside normative sources such as regulatory documents, corporate disclosures, and authoritative fatwas. The analysis highlights that BSI’s new persero status strengthens state capacity to position Islamic banking as a strategic development instrument, potentially enhancing scale, competitiveness, and financial inclusion. At the same time, it raises governance challenges, including risks of self-dealing, political intervention, and bureaucratic rigidity that may weaken market discipline. From a Shariah perspective, institutional legitimacy depends on substantive compliance, effective supervision by the Shariah Supervisory Board, and alignment with maqasid al-shariah objectives.